Self-compacting high-crack-resistance desert sand fiber recycled concrete and preparation method thereof
By using desert sand, recycled aggregates and fibers in concrete, the environmental pollution problems caused by poor crack resistance and high temperature preparation in the prior art are solved, and efficient and environmentally friendly concrete preparation is achieved.
Patent Information
- Application Number
- CN202510015450.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, self-finished concrete has poor crack resistance and requires high temperature during the preparation process, resulting in carbon dioxide emissions and environmental pollution.
Desert sand and recycled coarse aggregate are used to replace some river sand and natural aggregates, and combined with polyethylene fibers, fly ash and aluminum microbeads to prepare dense, high crack resistance desert sand fiber recycled concrete.
It improves the fluidity, self-solidity and crack resistance of concrete, reduces the demand for natural sand and gravel resources, reduces carbon emissions, and provides a sustainable treatment solution for construction waste.
Smart Images

Figure BDA0005229773130000151 
Figure BDA0005229773130000161 
Figure BDA0005229773130000162
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a self-compacting high-cracking-resistant desert sand fiber recycled concrete and a preparation method thereof. Background Art
[0002] With the development of infrastructure projects in my country, the demand for concrete continues to increase. The existing construction sand is difficult to meet the large demand for engineering construction. The natural sand and stone resources necessary for preparing concrete are becoming increasingly scarce. At the same time, the excessive exploitation of river sand has also caused certain environmental and ecological problems. However, my country's desert areas are vast, and the reserves of desert sand resources are large and concentrated. If it can be promoted and applied, it can not only solve the problem of scarce river sand resources and alleviate the desertification pressure in western my country, but also use local materials and reduce the transportation cost of raw materials. Experimental studies have shown that desert sand can optimize the aggregate grading and dense aggregate skeleton system in concrete, and can replace part of river sand for actual engineering. Its mechanical properties and failure forms are similar to those of ordinary concrete, and its seismic performance is better.
[0003] With the economic and social development of my country, a large number of original buildings have been demolished and rebuilt, generating a large amount of alkaline construction waste. If landfill treatment is adopted, the soil will become "inactivated", which will have an adverse impact on the ecological environment. The development of green buildings and high-performance concrete is the only way to optimize and upgrade building materials, and recycled concrete is a key research direction. In addition, recycled concrete is greatly affected by the quality and gradation of aggregates, and has the characteristics of low strength and elastic modulus, poor durability, etc. The high water absorption rate of recycled coarse aggregates makes the working performance of concrete worse.
[0004] If desert sand and recycled coarse aggregate can be used to replace part of the river sand and part of the natural aggregate respectively, and desert sand recycled concrete can be formulated for large-scale use in engineering projects, it will not only reduce the demand for natural sand and stone resources, but also provide a new solution for the disposal of waste concrete, bring significant economic benefits, save resources and protect the environment.
[0005] Patent No. CN108059410A (Patent 1) discloses a self-compacting concrete made by mixing water, cement, sand, stone, mineral admixtures, admixtures, ultrafine powders, and modifiers. The concrete prepared by the invention has a high gap passing rate and self-compacting ability, can flow freely, fully fill the internal space of the structure, and form a dense and uniform structure; and by adding ultrafine powder to the concrete, the fluidity of the concrete is further improved, while its compressive strength is increased.
[0006] Patent No. CN115626796A (Patent 2) discloses a recycled aggregate self-compacting concrete made by mixing recycled coarse aggregate, recycled fine aggregate, recycled micro-powder, fly ash, cement, carbide slag, vitrified micro-beads, water reducer and water. In the invention, the recycled micro-powder with higher activity is well combined with the vitrified micro-beads, fly ash and aggregate with higher strength, which ensures the anti-segregation property of the concrete, thereby further improving the durability and compressive strength of the concrete.
[0007] The above technologies have the following shortcomings: (1) Although the self-compacting concrete prepared in Patent 1 can improve the fluidity of concrete and increase its compressive strength, its crack resistance is poor and requires a large amount of sand. (2) The self-compacting concrete with recycled aggregate prepared in Patent 2 utilizes construction waste, but requires a high temperature of about 800°C during its preparation process, which will produce a large amount of carbon dioxide, causing new pollution, and there is a problem that the concrete is easy to crack.
[0008] Therefore, a new type of concrete is urgently needed to solve the above problems. Summary of the invention
[0009] The purpose of the present invention is to provide a self-compacting highly crack-resistant desert sand fiber recycled concrete and a preparation method thereof. The prepared concrete has the advantages of good performance, low price, low carbon emissions, good fluidity, self-compactness, high crack resistance, etc., and can solve the problems of shortage of construction sand and large-scale stacking of construction waste in the existing environment.
[0010] To achieve the above-mentioned purpose, the present invention provides a self-compacting highly crack-resistant desert sand fiber recycled concrete, which is composed of the following raw materials in parts by weight: 360-560 parts of cement; 90-140 parts of fly ash; fine aggregate: 204-320 parts of desert sand and 306-480 parts of ordinary river sand; coarse aggregate: 595-933 parts of natural aggregate and 595-933 parts of recycled aggregate; 0.72-1.12 parts of aluminum microbeads; 0.45-0.70 parts of water reducer; 4.5-7.0 parts of polyethylene fiber; and 180-280 parts of water.
[0011] Preferably, the cement is any one of ordinary Portland cement and composite Portland cement, and the 28-day compressive strength of the cement is not less than 42.5 MPa.
[0012] Preferably, the fly ash is Class I fly ash, with a moisture content of 0.1%, a loss on ignition of 1.91%, a particle size of 55 μm, and a specific surface area of not less than 400 m 2 / kg.
[0013] Preferably, the fineness modulus of desert sand is 1.0, and ordinary river sand is medium-coarse sand, and the fineness modulus of ordinary river sand is 2.5-3.5.
[0014] Preferably, the natural aggregate is mechanically crushed stone with a particle size range of 5 to 16 mm; the recycled coarse aggregate is made of pillars and construction waste removed from abandoned factory areas, which are crushed by a crusher and then sieved to prepare the recycled aggregate according to continuous grading with a particle size of 5 to 16 mm.
[0015] Preferably, the water reducer is a polycarboxylate water reducer.
[0016] Preferably, the aluminum microbeads have a particle size of 100 μm and an apparent density of 600 kg / m 3 .
[0017] Preferably, the polyethylene fiber has a length of 12 to 24 mm, a diameter of 20 to 30 μm, an aspect ratio of >500, an elongation at break of 2 to 3%, and a tensile strength of >2800 MPa.
[0018] The present invention also provides a method for preparing the self-compacting high crack resistance desert sand fiber recycled concrete as described above, comprising the following steps:
[0019] Step S1, weighing cement, fly ash, desert sand, ordinary river sand, natural aggregate, recycled aggregate, aluminum microbeads, water reducing agent, polyethylene fiber and water according to weight parts;
[0020] Step S2, placing cement, fly ash, desert sand, ordinary river sand, natural aggregate and recycled aggregate in a mixer and slowly stirring for 1 to 2 minutes to make the dry materials evenly mixed;
[0021] Step S3, after mixing the water reducing agent and water evenly, add them into a mixer and stir slowly for 1 to 2 minutes;
[0022] Step S4: After stirring evenly, add aluminum microbeads into the mixer and continue stirring slowly for 1 to 2 minutes;
[0023] Step S5, after the mixed material is stirred evenly, polyethylene fibers are added into the mixer to evenly disperse polyethylene fibers of different lengths to avoid agglomeration. After the polyethylene fibers are added, they are quickly stirred for 1 to 2 minutes;
[0024] Step S6, after the stirring is completed, pour it into a mold, vibrate it for 1 to 2 minutes to form it, and then seal it with a plastic film. After demolding, continue to cure for 28 days at a temperature of 20±2°C and a relative humidity of 40±5%, and obtain self-compacting high crack-resistant desert sand fiber recycled concrete.
[0025] Preferably, the rotation speed of slow stirring is 135-145 r / min, and the rotation speed of fast stirring is 275-295 r / min.
[0026] Therefore, the present invention adopts the above-mentioned self-compacting high crack resistance desert sand fiber recycled concrete and its preparation method, and the beneficial technical effects are as follows:
[0027] (1) Desert sand has a small particle size, large surface area, and low cohesion. It can act as a "ball" between cement and river sand, which helps to reduce internal friction, enhance the fluidity of concrete, and improve the working performance of concrete. In addition, the overall microscopic shape of desert sand particles is round, and there are very few needle-like particles. These round small particles can effectively reduce the porosity between aggregates and improve the grading of aggregates. Adding an appropriate amount of desert sand can compact the coarse and fine aggregate skeleton system of concrete. The fibers can be tightly connected with the concrete, improve the density, and improve the macroscopic performance of concrete.
[0028] (2) The present invention provides a self-compacting, highly crack-resistant desert sand fiber recycled concrete material and a preparation method thereof, which replaces a portion of natural river sand with desert sand and is added to concrete, greatly reducing the consumption of river sand and solving the problem of scarce sand resources for construction. In addition, the rational use of desert sand can effectively protect the natural environment, reduce the exploitation of natural river sand, and reduce carbon emissions.
[0029] (3) The polyethylene fiber added in the present invention has high tensile strength and tensile elastic modulus, and is often used to prepare high-strength ultra-high ductility concrete. Adding polyethylene fiber to concrete can improve the crack resistance of concrete; adding fly ash can improve the compactness and fluidity of concrete; adding aluminum microbeads can improve the fluidity and filling capacity of concrete, so that concrete can be self-leveling and self-compacting without vibration; adding high-efficiency water reducer allows cement particles to be evenly distributed, preventing flocculation between particles, thereby improving the fluidity and filling capacity of concrete. The present invention also uses recycled aggregate as coarse aggregate to be added to concrete. The addition of recycled aggregate not only reduces the amount of natural aggregate, but also provides a new solution for the treatment of construction waste, waste concrete, etc.
[0030] (4) The self-compacting high crack resistance desert sand fiber recycled concrete prepared by the present invention can make more full use of desert sand resources while maintaining the concrete performance unchanged. It reduces the dependence on river sand in concrete engineering, thereby reducing the environmental damage caused by excessive exploitation of river sand, rationally developing and effectively utilizing desert sand, alleviating the shortage of natural river sand resources, and realizing green exploitation and resource utilization of desert sand. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further illustrated by the following examples.
[0032] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0033] Embodiment 1
[0034] The mass ratio of each component of raw materials: 360kg cement; 90kg fly ash; fine aggregate: 204kg desert sand and 306kg ordinary river sand; coarse aggregate: 595kg natural aggregate and 595kg recycled aggregate; 0.72kg aluminum microbeads; 0.45kg water reducer; 4.5kg polyethylene fiber; 180kg water.
[0035] The cement used in the raw material is ordinary Portland cement, and the 28-day compressive strength is not less than 42.5MPa; the fly ash is Class I fly ash, with a moisture content of 0.1%, a loss on ignition of 1.91%, a particle size of 55μm, and a specific surface area of 500m 2 / kg; the fineness modulus of desert sand is 1.0, the fineness modulus of ordinary river sand is medium coarse sand, and the fineness modulus of ordinary river sand is 3.0; the particle size range of natural aggregate is mechanical crushed stone of 5-16mm; the recycled coarse aggregate is the pillars and construction waste removed from the waste factory area, which are crushed by a crusher and then sieved, and the recycled aggregate is prepared according to the continuous grading of particle size 5-16mm; the water reducer is polycarboxylate water reducer; the particle size of aluminum microbeads is 100μm, and the apparent density is 600kg / m 3 The length of the polyethylene fiber is 12 to 24 mm, the diameter is 20 to 30 μm, the aspect ratio is >500, the elongation at break is 2 to 3%, and the tensile strength is >2800 MPa.
[0036] Preparation method:
[0037] (1) First, cement, fly ash, desert sand, ordinary river sand, natural aggregate and recycled aggregate are placed in a cement mortar mixer and slowly stirred for 1 to 2 minutes at a speed of 140 r / min to make the dry materials evenly mixed;
[0038] (2) Mix the water reducer and water evenly and add them into a mixer. Stir slowly for 1 to 2 minutes at a speed of 140 r / min.
[0039] (3) After stirring evenly, add aluminum microbeads into the mixer and continue stirring slowly for 1 to 2 minutes at a speed of 140 r / min;
[0040] (4) After the mixed materials are stirred evenly, polyethylene fibers are added into the mixer to disperse polyethylene fibers of different lengths evenly to avoid agglomeration. After the polyethylene fibers are added, they are stirred rapidly for 1 to 2 minutes at a speed of 280 r / min.
[0041] (5) After the mixing is completed, it is poured into a mold, vibrated for 1 to 2 minutes, and then sealed with a plastic film. After demolding, it is continued to be cured for 28 days under indoor conditions (T = 20 ± 2 ° C, RH = 40 ± 5%) to obtain self-compacting high crack resistance desert sand fiber recycled concrete.
[0042] Embodiment 2
[0043] The mass ratio of each component of raw materials: 460kg cement; 115kg fly ash; fine aggregate: 263kg desert sand and 394kg ordinary river sand; coarse aggregate: 767kg natural aggregate and 767kg recycled aggregate; 0.92kg aluminum microbeads; 0.575kg water reducer; 5.75kg polyethylene fiber; 230kg water.
[0044] The cement used in the raw material is ordinary Portland cement, and the 28-day compressive strength is not less than 42.5MPa; the fly ash is Class I fly ash, with a moisture content of 0.1%, a loss on ignition of 1.91%, a particle size of 55μm, and a specific surface area of 500m 2 / kg; the fineness modulus of desert sand is 1.0, the fineness modulus of ordinary river sand is medium coarse sand, and the fineness modulus of ordinary river sand is 3.0; the particle size range of natural aggregate is mechanical crushed stone of 5-16mm; the recycled coarse aggregate is the pillars and construction waste removed from the waste factory area, which are crushed by a crusher and then sieved, and the recycled aggregate is prepared according to the continuous grading of particle size 5-16mm; the water reducer is polycarboxylate water reducer; the particle size of aluminum microbeads is 100μm, and the apparent density is 600kg / m 3 The length of the polyethylene fiber is 12 to 24 mm, the diameter is 20 to 30 μm, the aspect ratio is >500, the elongation at break is 2 to 3%, and the tensile strength is >2800 MPa.
[0045] Preparation method:
[0046] (1) First, cement, fly ash, desert sand, ordinary river sand, natural aggregate and recycled aggregate are placed in a cement mortar mixer and slowly stirred for 1 to 2 minutes at a speed of 140 r / min to make the dry materials evenly mixed;
[0047] (2) Then, mix the water reducer and water evenly and add them into a mixer. Stir slowly for 1 to 2 minutes at a speed of 140 r / min.
[0048] (3) After stirring evenly, add aluminum microbeads into the mixer and continue stirring slowly for 1 to 2 minutes at a speed of 140 r / min;
[0049] (4) After the mixed materials are stirred evenly, polyethylene fibers are added into the mixer to disperse polyethylene fibers of different lengths evenly to avoid agglomeration. After the polyethylene fibers are added, they are stirred rapidly for 1 to 2 minutes at a speed of 280 r / min.
[0050] (5) After the mixing is completed, it is poured into a mold, vibrated for 1 to 2 minutes, and then sealed with a plastic film. After demolding, it is continued to be cured for 28 days under indoor conditions (T = 20 ± 2 ° C, RH = 40 ± 5%) to obtain self-compacting high crack resistance desert sand fiber recycled concrete.
[0051] Embodiment 3
[0052] The mass ratio of each component of raw materials: 560kg cement; 140kg fly ash; fine aggregate: 320kg desert sand and 480kg ordinary river sand; coarse aggregate: 933kg natural aggregate and 933kg recycled aggregate; 1.12kg aluminum microbeads; 0.70kg water reducer; 7.0kg polyethylene fiber; 280kg water.
[0053] The cement used in the raw material is ordinary Portland cement, and the 28-day compressive strength is not less than 42.5MPa; the fly ash is Class I fly ash, with a moisture content of 0.1%, a loss on ignition of 1.91%, a particle size of 55μm, and a specific surface area of 500m 2 / kg; the fineness modulus of desert sand is 1.0, the fineness modulus of ordinary river sand is medium coarse sand, and the fineness modulus of ordinary river sand is 3.0; the particle size range of natural aggregate is mechanical crushed stone of 5-16mm; the recycled coarse aggregate is the pillars and construction waste removed from the waste factory area, which are crushed by a crusher and then sieved, and the recycled aggregate is prepared according to the continuous grading of particle size 5-16mm; the water reducer is polycarboxylate water reducer; the particle size of aluminum microbeads is 100μm, and the apparent density is 600kg / m 3 The length of the polyethylene fiber is 12 to 24 mm, the diameter is 20 to 30 μm, the aspect ratio is >500, the elongation at break is 2 to 3%, and the tensile strength is >2800 MPa.
[0054] Preparation method:
[0055] (1) First, cement, fly ash, desert sand, ordinary river sand, natural aggregate and recycled aggregate are placed in a cement mortar mixer and slowly stirred for 1 to 2 minutes at a speed of 140 r / min to make the dry materials evenly mixed;
[0056] (2) Mix the water reducer and water evenly and add them into the mixer. Continue to stir slowly for 1 to 2 minutes at a speed of 140 r / min.
[0057] (3) After stirring evenly, add aluminum microbeads into the mixer and continue stirring slowly for 1 to 2 minutes at a speed of 140 r / min;
[0058] (4) After the mixed materials are stirred evenly, polyethylene fibers are added into the mixer to disperse polyethylene fibers of different lengths evenly to avoid agglomeration. After the polyethylene fibers are added, they are stirred rapidly for 1 to 2 minutes at a speed of 280 r / min.
[0059] (5) After the mixing is completed, it is poured into a mold, vibrated for 1 to 2 minutes, and then sealed with a plastic film. After demolding, it is continued to be cured for 28 days under indoor conditions (T = 20 ± 2 ° C, RH = 40 ± 5%) to obtain self-compacting high crack resistance desert sand fiber recycled concrete.
[0060] Comparative Example 1:
[0061] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; water reducer 0.575kg; polyethylene fiber 5.75kg; water 230kg.
[0062] Compared with Example 2, the difference of Comparative Example 1 is that the raw material components do not contain aluminum microbeads, and the mass ratio of the remaining components is the same as that of Example 2. The preparation method is the same as that of Example 2.
[0063] Compared with Example 2, the concrete provided in this comparative example lacks aluminum microbeads, so the friction between concrete particles will increase, which will reduce the fluidity and self-compacting performance of the concrete.
[0064] Comparative Example 2:
[0065] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; glass microbeads 0.92kg; water reducer 0.575kg; polyethylene fiber 5.75kg; water 230kg.
[0066] Compared with Example 2, the difference of Comparative Example 2 is that glass microspheres are used to replace the same amount of aluminum microspheres in the raw material, and the remaining components and their mass ratios are the same as those in Example 2. The preparation method is the same as that in Example 2.
[0067] Compared with Example 2, although the glass microspheres in the concrete provided in this comparative example can improve the fluidity of the concrete, they cannot replace the aluminum microspheres and meet the strict requirements of strength and particle size at the same time.
[0068] Comparative Example 3:
[0069] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; ceramic microbeads 0.92kg; water reducer 0.575kg; polyethylene fiber 5.75kg; water 230kg.
[0070] Compared with Example 2, the difference of Comparative Example 3 is that ceramic microbeads are used to replace the same amount of aluminum microbeads in the raw material, and the remaining components and their mass ratios are the same as those in Example 2. The preparation method is the same as that of Example 2.
[0071] Compared with Example 2, although the ceramic microspheres in the concrete provided in this comparative example can improve the fluidity of the concrete, the strength of the ceramic microspheres is relatively low, which will adversely affect the strength of the concrete.
[0072] Comparative Example 4:
[0073] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; aluminum microbeads 0.92kg; water reducer 0.575kg; water 230kg.
[0074] Compared with Example 2, the difference of Comparative Example 4 is that the raw material components do not contain polyethylene fiber, and the remaining components and their mass ratios are the same as those in Example 2. The preparation method is the same as that in Example 2.
[0075] Compared with Example 2, the concrete provided in this comparative example lacks polyethylene fibers, so the tensile strength and crack resistance of the concrete are reduced, which has an adverse effect on the mechanical properties and working performance of the concrete.
[0076] Comparative Example 5:
[0077] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; aluminum microbeads 0.92kg; water reducer 0.575kg; polypropylene fiber 5.75kg; water 230kg.
[0078] Compared with Example 2, the difference of Comparative Example 5 is that polypropylene fiber is used to replace the polyethylene fiber of the same amount in the raw material, and the other components and their mass ratios are the same as those in Example 2. The preparation method is the same as that in Example 2.
[0079] Compared with Example 2, although the polypropylene fiber in the concrete provided in this comparative example can also improve the crack resistance of the concrete, the polypropylene fiber is a hydrophobic material and has poor bonding properties with the cement matrix, which will affect the density of the concrete and have an adverse effect on the working performance of the concrete.
[0080] Comparative Example 6:
[0081] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; aluminum microbeads 0.92kg; water reducer 0.575kg; glass fiber 5.75kg; water 230kg.
[0082] Compared with Example 2, the difference of Comparative Example 6 is that glass fiber is used to replace the same amount of polyethylene fiber in the raw material, and the other components and their mass ratios are the same as those in Example 2. The preparation method is the same as that in Example 2.
[0083] Compared with Example 2, the glass fiber in the concrete provided in this comparative example has good toughness, but the corrosion resistance of the glass fiber is poor, which will limit the application of the concrete in a corrosive environment.
[0084] Comparative Example 7:
[0085] The mass ratio of each component of raw materials: cement 460kg; fly ash 115kg; fine aggregate: ordinary river sand 657kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; aluminum microbeads 0.92kg; water reducer 0.575kg; polyethylene fiber 5.75kg; water 230kg.
[0086] Compared with Example 2, the difference of Comparative Example 7 is that ordinary river sand is used to replace the same amount of desert sand in the raw material, and the remaining components and their mass ratios are the same as those in Example 2. The preparation method is consistent with that in Example 2.
[0087] Compared with Example 2, the concrete provided in this comparative example lacks desert sand, so the internal friction of the concrete is increased, the fluidity and compactness of the concrete are reduced, and the mechanical properties and working performance of the concrete are adversely affected.
[0088] Comparative Example 8:
[0089] The mass ratio of each component of raw materials: cement 460kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; aluminum microbeads 0.92kg; water reducer 0.575kg; polyethylene fiber 5.75kg; water 230kg.
[0090] Compared with Example 2, the difference of Comparative Example 8 is that the raw material components do not contain fly ash, and the mass ratio of the other components is the same as that of Example 2. The preparation method is the same as that of Example 2.
[0091] Compared with Example 2, the concrete provided in this comparative example lacks fly ash, and the filling effect and ball effect of fly ash cannot be exerted, so the fluidity and compactness of the concrete are reduced, and the mechanical properties and working performance of the concrete are adversely affected.
[0092] Comparative Example 9:
[0093] The mass ratio of each component of raw materials: cement 460kg; fine aggregate: desert sand 263kg and ordinary river sand 394kg; coarse aggregate: natural aggregate 767kg and recycled aggregate 767kg; water reducer 0.575kg; polyethylene fiber 5.75kg; water 230kg.
[0094] Compared with Example 2, the difference of Comparative Example 9 is that the raw material components do not contain fly ash and aluminum microbeads, and the remaining components and their mass ratios are the same as those in Example 2. The preparation method is the same as that in Example 2.
[0095] Compared with Example 2, the concrete provided in this comparative example lacks fly ash and aluminum microspheres, and the filling effect and ball effect of fly ash and aluminum microspheres cannot be exerted, thereby reducing the durability and erosion resistance of the concrete, increasing the porosity of the concrete, reducing the fluidity of the concrete, and adversely affecting the mechanical properties and working performance of the concrete.
[0096] The self-compacting high crack-resistant desert sand fiber recycled concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 9 were respectively tested for slump expansion, compressive strength, splitting tensile strength and flexural strength. The size of the test blocks used in the compressive strength and splitting tensile strength tests was 100mm×100mm×100mm, and the size of the test blocks used in the flexural strength test was 100mm×100mm×300mm. The compressive strengths at 7d and 28d and the splitting tensile strength and flexural strength at 28d were measured respectively.
[0097] The experimental results are shown in the following table:
[0098] Table 1 Slump spread results
[0099] Test piece number Slump expansion / mm Embodiment 1 590 Embodiment 2 690 Embodiment 3 655 Comparative Example 1 610 Comparative Example 2 665 Comparative Example 3 640 Comparative Example 4 650 Comparative Example 5 630 Comparative Example 6 640 Comparative Example 7 620 Comparative Example 8 650 Comparative Example 9 600
[0100] Table 2 Compressive strength results
[0101]
[0102]
[0103] Table 3 Splitting tensile strength results
[0104] Test piece number Splitting tensile strength (28d) / MPa Embodiment 1 3.71 Embodiment 2 4.67 Embodiment 3 3.83 Comparative Example 1 3.73 Comparative Example 2 3.91 Comparative Example 3 3.85 Comparative Example 4 3.12 Comparative Example 5 3.80 Comparative Example 6 3.74 Comparative Example 7 3.84 Comparative Example 8 3.67 Comparative Example 9 3.51
[0105] Table 4 Flexural strength results
[0106]
[0107]
[0108] In summary, it can be seen that the slump expansion, compressive strength, splitting tensile strength and flexural strength of the self-compacting high crack-resistant desert sand fiber recycled concrete prepared by the present invention are significantly improved compared with conventional production modes and methods.
[0109] It is worth noting that the contents not elaborated in detail in the present invention are all prior art and are well known to those skilled in the art.
[0110] Therefore, the present invention adopts the above-mentioned self-compacting and highly crack-resistant desert sand fiber recycled concrete and its preparation method. The prepared concrete has the advantages of good performance, low price, low carbon emissions, good fluidity, self-compactness, high crack resistance, etc., which can solve the problems of shortage of construction sand and large-scale stacking of construction waste in the existing environment.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A self-compacting high crack resistance desert sand fiber recycled concrete, characterized in that: The invention is composed of the following raw materials in parts by weight: 360-560 parts of cement; 90-140 parts of fly ash; fine aggregate: 204-320 parts of desert sand and 306-480 parts of ordinary river sand; coarse aggregate: 595-933 parts of natural aggregate and 595-933 parts of recycled aggregate; 0.72-1.12 parts of aluminum microbeads; 0.45-0.70 parts of water reducer; 4.5-7.0 parts of polyethylene fiber; and 180-280 parts of water.
2. The self-compacting high crack resistance desert sand fiber recycled concrete according to claim 1, characterized in that: The cement is any one of ordinary silicate cement and composite silicate cement, and the 28-day compressive strength of the cement is not less than 42.5MPa.
3. The self-compacting high crack resistance desert sand fiber recycled concrete according to claim 1, characterized in that: The fly ash is Class I fly ash, with a moisture content of 0.1%, a loss on ignition of 1.91%, a particle size of 55 μm, and a specific surface area of not less than 400 m 2 / kg.
4. The self-compacting high crack resistance desert sand fiber recycled concrete according to claim 1, characterized in that: The fineness modulus of desert sand is 1.0, ordinary river sand is medium-coarse sand, and the fineness modulus of ordinary river sand is 2.5-3.
5.
5. The self-compacting high crack resistance desert sand fiber recycled concrete according to claim 1, characterized in that: The natural aggregate is mechanically crushed stone with a particle size range of 5 to 16 mm; the recycled coarse aggregate is made of pillars and construction waste removed from abandoned factory areas, which are crushed by a crusher and then sieved to prepare the recycled aggregate according to continuous grading with a particle size of 5 to 16 mm.
6. The self-compacting high crack resistance desert sand fiber recycled concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.
7. The self-compacting highly crack-resistant desert sand fiber recycled concrete according to claim 1, characterized in that: The particle size of aluminum microbeads is 100 μm and the apparent density is 600 kg / m 3 .
8. The self-compacting high crack resistance desert sand fiber recycled concrete according to claim 1, characterized in that: The polyethylene fiber has a length of 12 to 24 mm, a diameter of 20 to 30 μm, an aspect ratio of >500, an elongation at break of 2 to 3%, and a tensile strength of >2800 MPa.
9. A method for preparing the self-compacting highly crack-resistant desert sand fiber recycled concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, weighing cement, fly ash, desert sand, ordinary river sand, natural aggregate, recycled aggregate, aluminum microbeads, water reducing agent, polyethylene fiber and water according to weight parts; Step S2, placing cement, fly ash, desert sand, ordinary river sand, natural aggregate and recycled aggregate in a mixer and slowly stirring for 1 to 2 minutes to make the dry materials evenly mixed; Step S3, after mixing the water reducing agent and water evenly, add them into a mixer and stir slowly for 1 to 2 minutes; Step S4: After stirring evenly, add aluminum microbeads into the mixer and continue stirring slowly for 1 to 2 minutes; Step S5, after the mixed material is stirred evenly, polyethylene fibers are added into the mixer to evenly disperse polyethylene fibers of different lengths to avoid agglomeration. After the polyethylene fibers are added, they are quickly stirred for 1 to 2 minutes; Step S6, after the stirring is completed, pour it into a mold, vibrate it for 1 to 2 minutes to form it, and then seal it with a plastic film. After demolding, continue to cure for 28 days at a temperature of 20±2°C and a relative humidity of 40±5%, and obtain self-compacting high crack-resistant desert sand fiber recycled concrete.
10. A self-compacting high crack resistance desert sand fiber regeneration according to claim 9 The method for preparing concrete is characterized in that: The speed of slow stirring is 135~145r / min. The speed of rapid stirring is 275~295r / min.
Citation Information
Patent Citations
Self-compacting concrete and preparation method thereof
CN108059410A
Recycled aggregate self-compacting concrete
CN115626796A